Desenvolvimento de antena CPW em substrato têxtil em estrutura de malha para utilização em sistemas de indentificação por rádio frequência - Oliveira, Alexandre Henrique Soares de (2017)
The knitted fabrics have elastic, easy production and malleability properties, these characteristics be useful in the design of flexible antennas, that can be used in a RFID tag, for example. The mean objective of this work is development of antenna with a Coplanar Waveguide fed (CPW), in a textile knitted substrate, for use in active RFID systems in microwave frequency of 2.45 GHz. From the characterization of the electrical properties by a Vector Networks Analyzer and one with a Dielectric Probe kit, obtained the values of Electrical Permissiveness and Loss Tangent, in sequence was carried out the characterization of the textile properties of Linear Density, Basis weight, Dimensional stability and Tensile Strength, based on the data obtained in characterization process, was chosen two fabrics with properties favorable to the design, modeling and construction of antennas. After the selection of the tissues, simulations were performed on Ansys HFSStm (High Frequency Structural Simulator) to obtain the parameters of Return Loss, Radiation Diagram, Current Density, Impedance, Gain and VSWR, as well as dimensional optimization of the antennas. Two CPW-fed antennas were simulated, one on textile substrate made from Soybean Protein Fibers (SPF) and the other with Polypropylene with corn Polylactic Acid fibers (PP + PLA). Based on the simulations, two antennas with their respective textile substrates were constructed and using a vector network analyzer, the return loss and the impedance shown by the Smith Chart were measured. Both showed a return loss below -10dB for central design frequency and wide bandwidth. The simulated and measured results were compared, analyzing them according to the specialized reading in the area. Showing the feasibility of developing CPW antennas in knitted fabrics for active RFID systems, in addition to the possibility of interoperability in internet of things (IoT) communication systems